Biocatalysed acidification and metal leaching processes in sediments of polluted urban streams. (2014) - Porzionato, Natalia Florencia; Candal, Roberto; Curutchet, Gustavo
Sediments of fluvial streams are a sink for pollutants such as heavy metals and organic recalcitrant compounds. In anoxic conditions, sulphide generation and alkalinisation cause precipitation of heavy metals. The redox potential of the system could change to higher values, mainly owing to oxygen exposition generated by anthropogenic disturbances of the sediment such as dredging operations. Knowledge about the mechanisms involved is fundamental to assess the risk of acid generation and rise in heavy metals bioavailability. In this paper, the characterisation and assessment of acidification risk of sediments of a contaminated stream near Buenos Aires was carried out by static and kinetic assays. Speciation of heavy metals was determined after metal sequential extraction procedure. Also, re-suspension of sediments assay in batch mode, with and without Acidithiobacillus ferrooxidans inoculum, was carried out to assess the chemical changes that occur at oxygen exposure, verifying the acidification and heavy metal release processes.